DEVELOPMENT OF THE LITERACY MOVEMENT IN MADRASAH CURRICULUM MANAGEMENT - Baihaqi, Baihaqi; Mawardi, Imam (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The purpose of this research is so that madrasah can develop students' literacy skills optimally as expected by the government, can improve students' ethics and knowledge. The research method in this research uses qualitative research with descriptive methods. The data collection methods used were interviews and field observations. The results of this research state that the implementation of the School Literacy Movement in MI Muhammadiyah Gempolsewu in the 2022/2023 academic year is still very low. Indications of the implementation of the School Literacy Movement are visible, such as the existence of bookshelves in each class, but the existing books do not meet the standard number of school libraries. The ongoing literacy activities are not yet regular, they still run naturally in each class. In the lower grades, students enjoy reading before school hours. While the upper grades is more visible with smartphone facilities brought from home. A new finding in this research is the enthusiasm of students, especially the lower class, in literacy. They are 'thirsty' for books after not studying at school for two years due to the COVID-19 pandemic. In the upper class, students are introduced to digital literacy, where they bring their facilities from home, namely smartphones. This is to bridge the shortage of textbooks, introduce students to the internet, and use it for positive things. The main problem of implementing literacy at MI Muhammadiyah Gempolsewu is focused on the School Literacy Movement program which should be included in the madrasah curriculum so that its implementation can be directed and controlled.